(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The analysis of modern understanding of medical psychology as a field of professional activity of psychologists in medicine and public health is carried out, the main traditional and new directions of activity of a medical psychologist in clinical and preventive medicine are revealed. The main forms of work of a medical psychologist in healthcare institutions are presented, the role of a medical psychologist as part of a team of specialists is revealed; the analysis of the main models of multi-professional teams in the field of medical rehabilitation is carried out. The main problems in this area are identified, the solution of which is necessary for creating an effective system of providing medical and psychological care to the population. The integral role of a medical psychologist in the implementation of a multidisciplinary approach to providing assistance to patients and their relatives is shown, both in specialized psychiatric, drug treatment and psychotherapy, and in general medical practice.